EVALUATING LABORATORY WEBSITE USABILITY THROUGH THE SYSTEM USABILITY SCALE (SUS) - Ma'wa, Safarah Putri; Damayanti, Friska; Etruly, Niki (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: The Manual Drawing Laboratory and Computer Laboratory of the Furniture Design Study Program are some of the infrastructures used to support learning and practicum in the Polytechnic of Furniture Industry and Wood Processing. Services at these two laboratories utilize the Laboratory website which can be accessed publicly via the address https://labdesainfurnitur.poltek-furnitur.ac.id/, in which the purpose of developing the website is to simplify the process for stakeholders to access information regarding practicum activities conducted in the laboratories. Ease of access to this information needs to be evaluated, especially related to usability on the website. The evaluation of the laboratory website's usability is performed using the System Usability Scale (SUS) method, which provides a structured approach to measuring the effectiveness and user experience of the website. It is hoped to obtain a representation of the user's experience of the function and appearance of the laboratory website as advice on what features might be developed to improve the services. According to the results of data processing from 44 respondents, the average SUS score was 59.32. Based on this score, the Acceptability Range category is still in the marginal range, meaning there are still several things that need to be corrected or improved so the website can help in the daily operational activities of the laboratory. Keywords: laboratory; SUS; usability; user; website Abstrak: Laboratorium Gambar dan Laboratorium Komputer Program Studi Desain Furnitur merupakan sarana penunjang praktikum di Politeknik Industri Furnitur dan Pengolahan Kayu. Pelayanan pada kedua laboratorium ini telah memanfaatkan website yang dapat diakses secara publik melalui alamat https://labdesainfurnitur.poltek-furnitur.ac.id/, pemanfaatan website bertujuan untuk memudahkan para pengguna dalam memperoleh informasi seputar kegiatan praktikum di laboratorium di setiap waktu. Adanya pemanfaatan teknologi informasi tersebut perlu dievaluasi untuk mengetahui kegunaan website bagi para pengguna serta sebagai masukan untuk pengelola laboratorium dalam mengembangkan website di masa mendatang. Evaluasi website laboratorium dilakukan dengan metode System Usability Scale (SUS). Melalui evaluasi kegunaan pada website laboratorium diharapkan diperoleh representasi pengalaman pengguna terhadap fungsi dan tampilan website laboratorium dan diperoleh saran fitur-fitur yang dapat dikembangkan untuk meningkatkan pelayanan di laboratorium. Data yang diperoleh sebanyak 44 responden menghasilkan skor SUS dengan rata-rata 59,32. Berdasarkan skor tersebut, rentang akseptabilitas website masih berada pada rentang marginal, sehingga masih ada beberapa fitur yang perlu ditingkatkan agar website dapat membantu kegiatan operasional laboratorium sehari-hari. Kata kunci: kegunaan; laboratorium; pengguna; SUS; website